Math, asked by hitarthnaik8cris, 4 months ago

(w²+2)(y²+5)-6 simplify​

Answers

Answered by Anonymous
0

Answer:

5n(2n3+n2+8)+n(4-n).

5n(2n3+n2+8)+n(4-n).= 5n × 2n3 + 5n × n2 + 5n × 8 + n × 4 - n × n.

5n(2n3+n2+8)+n(4-n).= 5n × 2n3 + 5n × n2 + 5n × 8 + n × 4 - n × n.= 10n4 + 5n3 + 40n + 4n – n2.

5n(2n3+n2+8)+n(4-n).= 5n × 2n3 + 5n × n2 + 5n × 8 + n × 4 - n × n.= 10n4 + 5n3 + 40n + 4n – n2.= 10n4 + 5n3 + 44n – n2.

5n(2n3+n2+8)+n(4-n).= 5n × 2n3 + 5n × n2 + 5n × 8 + n × 4 - n × n.= 10n4 + 5n3 + 40n + 4n – n2.= 10n4 + 5n3 + 44n – n2.= 10n4 + 5n3 – n2 + 44n.

Similar questions